Perancangan Interior Kafe Basket di Surabaya - Clarissa Cindy Yossy; Adi Santosa; Anik Rakhmawati (Intra, 2016)
The enthusiasm towards Basketball is increasing in Surabaya. Sadly Surabaya has limited facilities for Basketball. Therefore, a café with basketball theme, which provides various basketball facilities, is designed to respond that problem. The café is designed to bring the atmosphere of basketball arena inside the room. The facilities provided are adapted from some facilities that existed in Basketball arena, so that visitors can experience the basketball arena while inside the café. The Interior Design of Basketball Café in Surabaya will be able to accommodate people’s needs in Surabaya, which are a place to deliver their hobby toward basketball as well as gaining some knowledge about Basketball. Visitors can enjoy basketball matches through a screen provided inside the café. They also can do basketball in the court, which also provided by the café. Visitors can also enjoy VIP facilities and purchase basketball accessories at the store.